The Cultural Environment of the Amarna Age of the First Egyptian Empire - Leonard, Paul A.
Ph.D.; University Microfilms Order No. 67-344. Microfilm $3.00; Xerography $9.70; Dissertation Abstracts 27/8 (Ann Arbor, Mich., February 1967) 2470-A.